Distinct Changes in Gut Microbiota of Patients with Kidney Graft Rejection - Visconti, Vanessa; Wirtz, Stefan; Schiffer, Mario; Müller-Deile, Janina (Transplantation Direct, 2024)
Background. Kidney graft rejection still represents the major cause of graft loss in kidney transplant recipients. Of growing interest is the bidirectional relationship between gut microbiome and immune system suggesting that gut microbiota can affect allograft outcome. Methods. In this cross-sectional case-control study, we characterized the gut microbial profile of adult renal transplant recipients with and without graft rejection to define a cohort-specific microbial fingerprint through 16S ribosomal RNA gene sequencing. We used very strict inclusion and exclusion criteria to address confounder of microbiota composition. Results. Different relative abundances in several gut microbial taxa were detectable in control patients compared with patients with kidney allograft rejection. Alpha diversity was lower in the rejection group and beta diversity revealed dissimilarity between patients with and without kidney graft rejection (P < 0.01). When the rejection group was stratified according to different types of allograft rejection, major changes were identified between patients with chronic T-cellular-mediated rejection and controls. Changes in alpha diversity within the gut microbiome were related to the probability of chronic T-cellular-mediated rejection (P < 0.05). Kidney transplant patients without rejection showed significant enrichment of rather anti-inflammatory taxa whereas in the rejection group bacteria well known for their role in chronic inflammation were increased. For example, amplicon sequence variant (ASV) 362 belonging to the genus Bacteroides and ASV 312 belonging to Tannerellaceae were enriched in no rejection (P < 0.001 and P < 0.01), whereas ASV 365 was enriched in patients with allograft rejection (P = 0.04). Looking at metagenomic functions, a higher abundance of genes coding for enzymes involved in bacterial multidrug resistance and processing of short-chain fatty acids was found in patients without rejection but an increase in enzymes involved in nicotinamide adenine dinucleotide phosphate production was seen in patients with allograft rejection. Conclusions. A distinct microbial fingerprint of patients with allograft rejection might serve as noninvasive biomarker in the future.
CRIS-Team Scopus Importer:2025-02-04